Tillage Study for Corn and Soybeans: Comparing Vertical, Deep, and No-Tillage - E. A. Adee (Kansas Agricultural Experiment Station Research Reports, 2019)
Trends from a tillage study conducted since 2011 have shown no clear differences between tillage systems for either corn or soybeans in lighter soils under irrigation. One out of seven years has shown a yield advantage for either corn or soybeans for any tillage system, which appears to be related to environmental conditions experienced during the season.
Keywords: vertical tillage; no-till; corn; soybeans; long-term tillage